2021
DOI: 10.1016/j.sjbs.2021.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Diacerein ameliorates kidney injury induced by cisplatin in rats by activation of Nrf2/Ho-1 pathway and Bax down-regulation

Abstract: Cisplatin is an antineoplastic medicine used for solid tumor treatment. The main side effect that limits its dose is nephrotoxicity. Diacerein has been used for the treatment of joint diseases like osteoarthritis. It also has exhibited analgesic effects and antipyretic activities in animal models so this study targets to indicate the diacerein effect on nephrotoxicity induced by cisplatin in rats. Rats were distributed into four groups: normal healthy control; diacerein, which received diacerein daily by gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The present work demonstrated that acute dose of APAP caused a marked increase in the activity of caspase-3 as well as the expression of Bax with diminished expression of Bcl-2 [ 42 ], that DIA therapy restored these results in a dose-related manner. The anti-apoptotic effect of DIA has been reported previously in different tissues [ 12 , 22 , 23 , 30 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 72%
“…The present work demonstrated that acute dose of APAP caused a marked increase in the activity of caspase-3 as well as the expression of Bax with diminished expression of Bcl-2 [ 42 ], that DIA therapy restored these results in a dose-related manner. The anti-apoptotic effect of DIA has been reported previously in different tissues [ 12 , 22 , 23 , 30 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 72%
“…This indicates the beneficial effect of DIA in reducing the fibrosis which agrees with Barakat and his colleges. 69…”
Section: Discussionmentioning
confidence: 99%
“…In investigations carried out in vitro and in vivo on animals and humans, Rhein, the active metabolic form of Diacerhein, has been demonstrated to decrease the manufacture and activity of proin ammatory cytokines, particularly IL-1β [29,47] . In addition, the substance directly affects in ammatory cells by preventing human neutrophils from producing superoxide anion, lysosomal enzyme release, chemotaxis, and phagocytic activity.…”
Section: Discussionmentioning
confidence: 99%